A cadeia produtiva da erva mate em Turvo PR: Programa Ecomate - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
This dissertation, whose spatial scope covers the rural space of the Municipality of Turvo, in Paraná (PR), its general theme is the Ecomate Program implemented by the City Hall of Turvo PR, through the municipal Department of Agriculture and Livestock, starting in 2018. The research aims to understand the importance of the Program for the municipal economy, since yerba mate is a strong source income for local family farmers. The ecomate Program aims to select producers and provide technical guidance from planting to harvesting yerba mate. Yerba mate planting must be carried out exclusively in shaded areas, without degrading native forests. The innovative proposal aims to boost productive activity in the region, while contributing to the conservation and preservation of the municipality's biodiversity. By planting yerba mate in shaded areas, rural producers participating in the program guarantee the protection of local flora and fauna, establishing a balance between economic activity and environmental responsibility. The research remains open for future study, for implementation in other municipalities in Paraná, always with a view to improving the quality and quantity of yerba mate produced by producers. To this end, field research was carried out on properties that are part of the Ecomate program, also in the municipality's traditional communities, indigenous, quilombolas and faxinalenses. And, based on the data collection, interviews were carried out with yerba mate manufacturers in the municipality.
Keywords: erva´-mate; programa ecomate; sustentabilidade; comunidades tradicionais.; yerba mate; ecomate program; sustainability; traditional communitie; Gestão de Território